The effect of using blast furnace slag on strength of concrete in hot weather - Ibrahim , Ahmad J. (Al-Mukhtar Journal of Sciences, 2010)
The paper investigates the effect of hot weather condition on the flexural and compressive strength of concrete, containing different percentages of blast furnace slag as partial replacement of cement used in concrete mixes. The results indicate that concrete containing blast furnace slag as a partial replacement of cement (up to 40%) cast and curded in hot weather have about the same compressive and flexural strength at 90 days, as those made with ordinary Portland cement alone cast and curded in the same condition.